Integrated provenance and detrital thermochronology studies on the ANDRILL AND-2A drill core: Late Oligocene-Early Miocene exhumation of the Transantarctic Mountains (southern Victoria Land, Antarctica) - ZATTIN, MASSIMILIANO; TALARICO FM; SANDRONI S. (Terra Nova, 2010)
Detrital apatite fission-track data combined with provenance analysis of gravel-fraction detritus are used in this study to investigate the Neogene exhumation of the West Antarctic Rift System. Samples have been collected from the upper 1000 m of the ANDRILL AND-2A drill core, which documents the Miocene history of the Victoria Land Basin. Most samples have apatites with fission-track ages between 23 and 36 Ma and gravel clasts derived from the Erebus Volcanic Province and the Transantarctic Mountains exposed along the southern Victoria Land coast. These results indicate the existence of a so far undetected Oligocene ⁄ Early Miocene exhumation phase in the region between the Blue–Koettlitz and Skelton–Mulock glaciers, suggesting the importance of fluctuation of local glaciers in the Royal Society Range and ⁄ or expansions into the McMurdo Sound of an ice sheet mainly sourced by larger outlet glaciers located further south.